Carbon nanotube / tin disulfide carbon composite material and preparation method and application thereof
By using carbon nanotube/tin disulfide@carbon composite materials in lithium-ion batteries, the cladding layer is formed through carbon nanotube activation treatment and hydrothermal reaction, the problem of tin disulfide volume changes is solved, and the lithium-ion battery is significantly improved The electrochemical and cyclic properties meet the needs of high energy density.
Patent Information
- Application Number
- CN202310729292.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-06-19
- Publication Date
- 2024-12-20
AI Technical Summary
The specific capacity and energy density of the negative electrode materials of existing lithium-ion batteries cannot meet the rapidly developing demand for mobile electronic equipment, and the volume of tin disulfide as the negative electrode material changes greatly, affecting the electrochemical performance.
Carbon nanotubes/tin disulfide@carbon composite materials are used as the negative electrode material, tin disulfide is grown through carbon nanotube activation treatment and hydrothermal reaction, and carbonized at high temperature in the carbon layer precursor solution to form a carbon layer with a thickness of 3-10nm , coated with tin disulfide, forming a three-dimensional core-shell structure and a rich pore structure, inhibiting the volume expansion of tin disulfide.
Significantly improve the electrochemical performance of lithium-ion batteries, improve the lithium storage capacity and rate performance, and maintain good cycling performance. For example, after cycling at a current density of 1A/g for 200 weeks, it can still obtain a higher capacity, and promote the actual tin disulfide application.
Smart Images

Figure CN119170754A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of negative electrode materials, in particular to a preparation technology of negative electrode materials for lithium ion batteries, and further to a carbon nanotube / tin disulfide@carbon composite material and a preparation method and application thereof. Background Art
[0002] Lithium-ion batteries are widely used secondary batteries that are closely related to human daily life and have attracted much attention. In the face of the increasing demand for battery life, researchers are actively exploring the development of lithium-ion batteries with higher energy density. The specific capacity and energy density of currently commercialized graphite-based carbon negative electrode materials can no longer meet the requirements of rapidly developing mobile electronic devices. Therefore, the development of new lithium-ion battery negative electrode materials with high specific capacity and cycle life has become one of the focuses of current research work.
[0003] When tin disulfide is used as the negative electrode material of lithium-ion batteries, the theoretical capacity is as high as (1232mAh g -1 ), but its volume change is larger (420%).
[0004] Chinese patent application CN111384387A discloses a lithium-ion battery and its preparation method, which introduces a method for preparing a MOF-coated tin disulfide-loaded Mxene composite material, which has a high capacity at a low current density. However, the material preparation method of this scheme is complicated, and the conductivity problem after MOF-coated tin disulfide has not been studied in detail. Summary of the invention
[0005] The present invention provides a carbon nanotube / tin disulfide@carbon composite material and a preparation method and application thereof. The carbon nanotube / tin disulfide@carbon composite material provided by the present invention is used as a negative electrode material, especially as a negative electrode material for a lithium ion battery, which can improve the electrochemical performance of the lithium ion battery.
[0006] To achieve the purpose, the present invention provides the following technical solutions:
[0007] In one aspect, the present invention provides a method for preparing a carbon nanotube / tin disulfide@carbon composite material, the preparation method comprising the following steps:
[0008] 1) activating the carbon nanotubes in hydrochloric acid;
[0009] 2) in-situ growing tin disulfide on the carbon nanotubes treated in step 1) by a hydrothermal reaction to obtain a carbon nanotube / tin disulfide substrate;
[0010] 3) subjecting the carbon nanotube / tin disulfide substrate to a hydrothermal reaction in a carbon layer precursor solution having a concentration of 0.2-2.0 mol / L (e.g., 0.2, 0.3, 0.4, 0.5, 1.0, 1.5, 2.0 mol / L, etc.), and then subjecting the substrate to high temperature carbonization at 200-500°C (e.g., 200°C, 300°C, 400°C, 500°C, etc.) under an inert atmosphere, so that the surface of the substrate is coated with a carbon layer to obtain the composite material; wherein the carbon layer precursor is selected from one or both of glucose and sucrose, preferably glucose.
[0011] In the preparation method of the present invention, the carbon nanotubes are first activated with hydrochloric acid, and then tin disulfide is in situ grown on the carbon nanotubes by hydrothermal reaction to obtain a carbon nanotube / tin disulfide substrate, and then the substrate is mixed with a glucose and / or sucrose solution of a specific concentration (0.2-2.0 mol / L) for hydrothermal reaction and high-temperature carbonization, so that a 2-10 nm thick carbon layer can be coated on the surface of the substrate; the composite material obtained by the method has a three-dimensional core-shell structure and a rich pore structure, and the composite material is particularly suitable for use as a negative electrode material, especially suitable for use as a negative electrode material in lithium ion batteries, and can effectively inhibit the volume expansion of tin disulfide, can significantly improve the electrochemical performance of lithium ion batteries, and on the basis of improving the lithium storage capacity, can take into account the improvement of the rate performance, and show good cycle performance in the cycle performance test, for example, at a current density of 1A / g, after 200 cycles, a higher capacity can still be obtained. The composite material developed based on the method of the present invention is conducive to further promoting the practical application of tin disulfide.
[0012] In a preferred embodiment, in step 2), the hydrothermal reaction comprises: mixing a mixture of tin tetrachloride pentahydrate and thioacetamide with the carbon nanotubes treated in step 1), and performing a hydrothermal reaction at 100-200°C (e.g., 100°C, 120°C, 150°C, 180°C, 200°C, etc.), thereby in situ growing the tin disulfide on the surface of the carbon nanotubes to obtain the carbon nanotube / tin disulfide substrate.
[0013] In a preferred embodiment, in step 2), the mass ratio of the mixture of tin tetrachloride pentahydrate and thioacetamide to the carbon nanotubes is 1:0.1-1:1 (e.g., 1:0.1, 1:0.3, 1:0.5, 1:0.8, 1:1, etc.); the inventors have found that the preferred carbon nanotube addition ratio is conducive to the good dispersion of the carbon nanotubes and can effectively avoid the agglomeration of the carbon nanotubes, thereby avoiding the problem that tin disulfide cannot grow well in situ on the surface of the carbon nanotubes during the hydrothermal reaction due to agglomeration; on the other hand, it can promote the improvement of the conductivity of tin disulfide, prevent the agglomeration of tin disulfide, and further significantly improve the electrochemical performance of tin disulfide as a negative electrode material.
[0014] Preferably, in the mixture of tin tetrachloride pentahydrate and thioacetamide, the mass ratio of the tin tetrachloride pentahydrate to the thioacetamide is 1:0.6-1:1.5, for example, 1:0.6, 1:0.8, 1:1.0, 1:1.3, 1:1.5, etc.
[0015] In some embodiments, in step 2), the reaction time of the hydrothermal reaction is 10-24 hours, for example, 10 hours, 15 hours, 20 hours, 24 hours, etc.
[0016] In a preferred embodiment, in the step 1), the activation treatment comprises: mixing the carbon nanotubes with hydrochloric acid at a mass ratio of 0.5:1-1:1, treating in an air atmosphere for 1-6 hours, then washing with deionized water, and centrifuging to obtain the activated carbon nanotubes. Carrying out the activation treatment of the carbon nanotubes under the preferred conditions can enable the carbon nanotubes to obtain a better activation pore-forming effect, and facilitates a more thorough removal of impurities that may exist therein, thereby facilitating the acquisition of a negative electrode material with better performance.
[0017] Preferably, the activation treatment is carried out at room temperature.
[0018] Preferably, the concentration of the hydrochloric acid is 0.2-1 mol / L.
[0019] In some embodiments, in step 3), the high temperature carbonization is performed for 1-6 hours, such as 1 hour, 3 hours, 5 hours, 6 hours, etc.
[0020] In some embodiments, in step 3), the temperature of the hydrothermal reaction is 100-200°C (e.g., 100°C, 120°C, 150°C, 180°C, 200°C, etc.), and the reaction time is preferably 10-24 hours (e.g., 10 hours, 15 hours, 20 hours, 24 hours, etc.).
[0021] In the present invention, the obtained carbon nanotube / tin disulfide substrate is subjected to hydrothermal reaction and high-temperature carbonization in a glucose and / or sucrose solution of a specific concentration (0.2-2.0 mol / L), and a carbon coating layer with a carbon layer thickness of 2-10 nm can be formed on the surface of the substrate. The inventors have found that if the concentration of the glucose and / or sucrose solution is too high, the formed carbon layer is too thick, which will seriously affect the ionic conductivity (D Li+ ), which is not conducive to improving the electrochemical performance; if the concentration is too low, the carbon layer coated on the surface of the carbon nanotube / tin disulfide substrate will be too thin, the carbon layer thickness will be too low, and the carbon layer formed after the carbonization of glucose / sucrose will be insufficient to completely coat the CNT / SnS2. During the charge and discharge cycle, the SnS2 that is not well coated will directly contact with the electrolyte to form an unstable solid electrolyte interface film, consuming the electrolyte; at the same time, it will not play a significant role in the volume expansion of tin disulfide during the charge and discharge cycle.
[0022] In the present invention, the carbon layer precursor in the carbon layer precursor solution is one or both of glucose and sucrose, preferably glucose. The inventors have found that the composite material obtained by using glucose as a negative electrode material in a lithium-ion battery can obtain better electrochemical performance than that of sucrose. The solvent in the carbon layer precursor solution is specifically deionized water. In step 3), the amount of the carbon layer precursor solution is excessive, and there is no particular restriction on its specific amount. Specifically, in some embodiments, relative to 200 mg of carbon nanotube / tin disulfide substrate, the amount of the carbon layer precursor solution can be, for example, 35-40 ml.
[0023] The inert atmosphere in step 3) is, for example, an argon atmosphere.
[0024] Preferably, in step 3), the thickness of the carbon layer is 2-10 nm.
[0025] Another aspect of the present invention provides a carbon nanotube / tin disulfide@carbon composite material, the composite material comprises a carbon nanotube / tin disulfide substrate, the surface of the substrate is coated with a carbon layer, preferably the thickness of the carbon layer is 2-10nm, for example 2, 3, 4, 5, 6, 7, 8, 9, 10nm, etc.;
[0026] Preferably, the carbon nanotube / tin disulfide substrate is obtained by in-situ growing tin disulfide on the surface of carbon nanotubes;
[0027] Preferably, the carbon layer is formed by carbonization of glucose and / or sucrose, preferably the carbon layer is formed by carbonization of glucose;
[0028] Further preferably, the composite material is prepared by the preparation method described above.
[0029] The present invention also provides the carbon nanotube / tin disulfide@carbon composite material prepared by the preparation method described above or the use of the carbon nanotube / tin disulfide@carbon composite material described above, wherein the composite material is used as a negative electrode material, preferably as a negative electrode material for a lithium ion battery.
[0030] The present invention also provides a lithium ion battery, wherein the negative electrode material used in the lithium ion battery comprises the carbon nanotube / tin disulfide@carbon composite material prepared by the preparation method described above or the carbon nanotube / tin disulfide@carbon composite material described above.
[0031] The technical solution provided by the present invention has the following beneficial effects:
[0032] The carbon nanotube / tin disulfide@carbon composite material prepared by the preparation method of the present invention is used as a negative electrode material in batteries, especially in lithium-ion batteries, and can significantly inhibit the volume expansion of tin disulfide. At the same time, it can be beneficial to the infiltration of electrolyte and ion transmission, and it is beneficial to improve the ion diffusion coefficient, so that the electrochemical performance can be significantly improved. On the basis of improving the lithium storage capacity, it can also improve the rate performance and has better cycle performance. For example, a relatively high capacity can still be obtained after 200 cycles at a current density of 1 A / g, which can further promote the practical application of tin disulfide.
[0033] The preparation method provided by the invention has simple process and is easy to implement and operate. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 The carbon nanotube / tin disulfide substrate (corresponding to Figure 1 Middle (a), (b)) and composite materials (corresponding Figure 1 The pore structure test results in the middle figures (c) and (d).
[0035] Figure 2 Shown is a scanning electron microscope photograph of the composite material in Example 1.
[0036] Figure 3 Shown is a scanning electron microscope photograph of the composite material in Comparative Example 9. DETAILED DESCRIPTION
[0037] In order to facilitate the understanding of the present invention, the present invention will be further described below in conjunction with examples. It should be understood that the following examples are only for a better understanding of the present invention and do not mean that the present invention is limited to the following examples.
[0038] Where specific experimental steps or conditions are not specified in the examples, the corresponding conventional experimental steps or conditions in the art can be used. The reagents or instruments used without specifying the manufacturer are all conventional products that can be purchased commercially.
[0039] Description of the test method:
[0040] Thickness of carbon layer: Disperse CNT / SnS2@C composite material into ethanol solution to form dispersion, add 10ml centrifuge tube and perform ultrasonic treatment in ultrasonic cleaner for 1 hour. In order to prevent the sample from settling at the bottom of the centrifuge tube, shake the centrifuge tube several times during this period. After the end of ultrasonic treatment, absorb the dispersion with a capillary and contact it with the carbon film used for testing transmission electron microscopy. After the dispersion in the capillary flows out, slowly remove the capillary, and then put the carbon film into a vacuum drying oven for drying, and finally put it into the transmission electron microscope sample chamber for testing. CNT, SnS2 and C can be seen in the transmission electron microscope photos respectively. The outermost layer is the carbon layer. The thickness of the carbon layer can be determined by measuring with a scale.
[0041] Pore structure test: BET and pore structure analysis were performed on a Micromeretics ASAP 2010 analyzer. Test conditions include: using N2 as the adsorbate, adsorption at liquid nitrogen temperature (77K), and measuring the specific surface area by the BET method, with a linear range of P / P0 = 0.05-0.3, where P0 is the saturated vapor pressure of the adsorbate at the experimental temperature, and P is the equilibrium pressure during adsorption. Test steps: After degassing at 300°C for 3h, perform the BET test.
[0042] Morphology characterization: The morphology was characterized using a JEOL JEM-ARN 200F spherical aberration corrected transmission electron microscope.
[0043] Example 1: CNT / SnS2@C composite material with a carbon layer thickness of 3 nm
[0044] The preparation steps include:
[0045] 1) Mix carbon nanotubes and hydrochloric acid with a mass concentration of 0.5 mol / L in a mass ratio of 0.6:1, and perform activation treatment at room temperature in an air atmosphere for 3 hours. After the activation treatment, centrifuge and wash with deionized water to wash away the residual hydrochloric acid, thereby obtaining activated carbon nanotubes.
[0046] 2) Tin tetrachloride pentahydrate and thioacetamide were mixed in a mass ratio of 1:0.86 to obtain a mixture (corresponding to the "mixture" in Table 1), and the mixture was mixed with the carbon nanotubes treated in step 1) in a mass ratio of 1:0.1, and a hydrothermal reaction was carried out at 150° C. for 10 hours, thereby in situ growing tin disulfide on the surface of the carbon nanotubes to obtain a carbon nanotube / tin disulfide substrate.
[0047] 3) placing the substrate obtained in step 2) in a glucose aqueous solution with a concentration of 0.2 mol / L (the mass volume ratio of the substrate to the glucose aqueous solution is about 200 / 35≈5.7, unit: mg / ml), performing a hydrothermal reaction at 180°C for 12 hours, and then performing high-temperature carbonization at 300°C for 1 hour under an argon atmosphere to form a carbon coating layer (i.e., a carbon layer) on the surface of the substrate to obtain a composite material, wherein the thickness of the carbon coating layer is 3 nm.
[0048] The carbon nanotube / tin disulfide substrate obtained in step 2) and the composite material obtained in step 3) were tested for pore structure. The results are as follows: Figure 1 As shown in Figures (a) and (b) are the results of the carbon nanotube / tin disulfide substrate, and Figures (c) and (d) are the results of the composite material. As can be seen from Figures a and c, after the carbon layer is coated in step 3), the specific surface area is increased from 61.4 m2 to 61.4 m2 of the substrate obtained in step 2). 2 g -1 Increased to 118.7m 2 g -1 , forming a rich pore structure. As can be seen from Figures b and d, the materials before and after coating have microporous and mesoporous structures. After coating, the specific surface area increases, that is, the pore structure becomes richer, and both micropores and mesopores increase, which is conducive to the penetration of electrolyte into the electrode and ion transport.
[0049] Example 2: CNT / SnS2@C composite material with a carbon layer thickness of 6 nm
[0050] The composite material was prepared by referring to Example 1, except that some preparation conditions were changed. Please refer to Table 1 for details.
[0051] Example 3: CNT / SnS2@C composite material with a carbon layer thickness of 9 nm
[0052] The composite material was prepared by referring to Example 1, except that some preparation conditions were changed. Please refer to Table 1 for details.
[0053] Table 1
[0054]
[0055] Example 4
[0056] The process is carried out in accordance with Example 1, except that in step 3), the glucose solution is replaced by sucrose solution.
[0057] Comparative Example 1: Pure SnS2
[0058] The preparation steps include: adding 0.7g of tin tetrachloride pentahydrate into a beaker containing 25mL of 95wt% ethanol aqueous solution, stirring for 0.5 hours to form solution A. Adding 0.6g of thioacetamide into a beaker containing 25mL of 95wt% ethanol aqueous solution, stirring for 0.5 hours to form solution B. After the two solutions are mixed, they are fully stirred, and then the mixed solution is poured into a 100ml Teflon-lined stainless steel autoclave, and kept at 160°C for 12 hours, cooled naturally to room temperature, washed with ethanol and deionized water, and dried to obtain pure SnS2.
[0059] Comparative Example 2: CNT / SnS2
[0060] The carbon nanotubes (CNT) were activated according to step 1) of Example 1 to obtain activated CNTs.
[0061] Then, 50 mg of activated CNT and 0.7 g of tin tetrachloride pentahydrate were added to a beaker containing 25 mL of 95 wt% ethanol aqueous solution, and stirred for 0.5 hours to form solution A. 0.6 g of thioacetamide was added to a beaker containing 25 mL of 95 wt% ethanol aqueous solution, and stirred for 0.5 hours to form solution B. After the two solutions were mixed, they were fully stirred, and then the mixed solution was poured into a 100 ml Teflon-lined stainless steel autoclave, and kept at 160 ° C for 12 hours. After naturally cooling to room temperature, it was washed with ethanol and deionized water and dried to obtain CNT / SnS2.
[0062] Comparative Example 3: CNT
[0063] The carbon nanotubes (CNT) were activated according to step 1) of Example 1 to obtain the CNTs required for Comparative Example 3.
[0064] Comparative Example 4: Glucose-derived Carbon
[0065] The preparation steps include: weighing glucose (manufacturer: Aladdin, CAS: 50-99-7, purity: analytical grade) and placing it in a clean crucible, then placing the crucible in a tubular furnace, and under the protection of an inert gas (argon), heating the temperature to 450°C at a rate of 2°C / min, and keeping the temperature at this temperature for 3 hours. After the tubular furnace is naturally cooled to room temperature, the crucible is taken out of the tubular furnace to obtain a glucose-derived carbon material.
[0066] Comparative Example 5: SnS2@C
[0067] The preparation steps include:
[0068] Pure tin disulfide was prepared by referring to Comparative Example 1;
[0069] 0.2g of prepared pure tin disulfide was added to 35ml of glucose aqueous solution with a concentration of 0.3mol / L, and magnetically stirred for 0.5 hours. The mixed solution was transferred to a stainless steel autoclave with a volume of 100ml, kept at 180℃ for 12 hours, cooled naturally to room temperature, and then centrifuged and dried. Finally, the dried product was placed in a tubular furnace for annealing: under the protection of inert gas (argon), kept at 450℃ for 3 hours, and then cooled naturally to room temperature to obtain SnS2@C composite material.
[0070] Comparative Example 6:
[0071] The method was carried out in accordance with Example 1, except that the concentration of the glucose aqueous solution used in step 3) was 0.1 mol / L. The carbon layer thickness of the obtained composite material was less than 2 nm.
[0072] Comparative Example 7:
[0073] The method was carried out in accordance with Example 1, except that the concentration of the glucose aqueous solution used in step 3) was 3.0 mol / L. The carbon layer thickness of the obtained composite material was greater than 10 nm.
[0074] Comparative Example 8:
[0075] The process is carried out in accordance with Example 1, except that in step 2), the mass ratio of the mixture of tin tetrachloride pentahydrate and thioacetamide to the carbon nanotubes is 1:0.05.
[0076] Comparative Example 9:
[0077] The process is carried out in accordance with Example 1, except that in step 2), the mass ratio of the mixture of tin tetrachloride pentahydrate and thioacetamide to the carbon nanotubes is 1:1.5.
[0078] The composite materials of the above examples and the materials of the comparative examples were used as negative electrode materials, and lithium ion batteries (button batteries) were prepared according to conventional methods for performance testing. Specifically, the preparation process of the button batteries is as follows:
[0079] The negative electrode material was mixed with the conductive carbon black Super P and the binder polyvinylidene fluoride (PVDF) in a mass ratio of 80:10:10, and the solvent N-methylpyrrolidone (NMP) (the amount of the solvent was 60wt%) was added to form a uniform negative electrode slurry. The negative electrode slurry was evenly coated on the copper foil with a coating machine and vacuum dried to obtain a negative electrode sheet. The obtained negative electrode sheet was cut into a disc with a diameter of 12mm and placed in an MBraun2000 glove box (Ar atmosphere, H2O and O2 concentrations less than 0.1×10 -6Volume %) for standby use, with a metal lithium sheet as the reference electrode, the aforementioned disc as the negative electrode, and a 1M LiPF6 solution (the solvent is a mixed solvent with a volume ratio of DEC (diethyl carbonate): EC (ethylene carbonate) = 1:1) as the electrolyte, assembled into a button cell. The battery capacity and initial efficiency were tested by the battery test system CT2001A battery tester of Wuhan Blue Electric Electronics Co., Ltd., with a current of 0.1C (1C = 1232mAh / g) and a voltage of 0.01-3V. The test results are summarized in Table 2.
[0080] Table 2
[0081]
[0082]
[0083] From the experimental results of Table 2, it can be seen that the carbon nanotube / tin disulfide@carbon composite material obtained by the preparation method of the present invention has good electrochemical performance when applied to lithium ion batteries as a negative electrode material. Compared with each comparative example, it can take into account a higher discharge capacity, first coulomb efficiency and cycle performance, and can maintain an extremely high capacity level after 200 cycles at a current density of 1A / g. From the experimental results of Examples 1-3 and 4, the composite material obtained by using glucose has better electrochemical performance than that of sucrose. From the experimental results of the embodiment and comparative examples 6 and 7, the concentration of the glucose aqueous solution in step 3) of the embodiment is controlled at 0.2-2.0moL / L, and the obtained composite material has significantly better electrochemical performance than the composite material obtained in comparative examples 6 and 7. Preferably, the mass ratio of the mixture of tin tetrachloride pentahydrate and thioacetamide to the carbon nanotube in step 2) is controlled at 1:0.1-1:1, which has better electrochemical performance than comparative examples 8 and 9.
[0084] In addition, the inventors conducted a scanning electron microscope test on the composite material obtained in the example and found that in the composite material obtained in the example, the carbon nanotubes were well dispersed and the tin disulfide was not easy to agglomerate. Figure 2 Taking the scanning electron microscope photo of the composite material in Example 1 as an example, it can be seen that the carbon nanotubes are well dispersed and the tin disulfide is not easy to agglomerate. Figure 3 The scanning electron microscope photograph of Comparative Example 9 shows that tin dioxide is severely aggregated on the surface of carbon nanotubes, which has an impact on the improvement and enhancement of electrochemical performance.
[0085] It is easy to understand that the above embodiments are only examples for clear explanation and do not mean that the present invention is limited thereto. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from this are still within the protection scope of the present invention.
Claims
1. A method for preparing a carbon nanotube / tin disulfide@carbon composite material, characterized in that: The preparation method comprises the following steps: 1) activating the carbon nanotubes in hydrochloric acid; 2) in-situ growing tin disulfide on the carbon nanotubes treated in step 1) by a hydrothermal reaction to obtain a carbon nanotube / tin disulfide substrate; 3) subjecting the carbon nanotube / tin disulfide substrate to a hydrothermal reaction in a carbon layer precursor solution with a concentration of 0.2-2.0 mol / L, and then subjecting the substrate to high temperature carbonization at 200-500°C in an inert atmosphere, so that the surface of the substrate is coated with a carbon layer, thereby obtaining the composite material; wherein the carbon layer precursor is selected from one or both of glucose and sucrose, preferably glucose.
2. The preparation method according to claim 1, characterized in that: In step 2), the hydrothermal reaction comprises: Mixing the mixture of tin tetrachloride pentahydrate and thioacetamide with the carbon nanotubes treated in step 1), and performing a hydrothermal reaction at 100-200° C., thereby in-situ growing the tin disulfide on the surface of the carbon nanotubes to obtain the carbon nanotube / tin disulfide substrate; Preferably, in step 2), the hydrothermal reaction time is 10-24 hours.
3. The preparation method according to claim 2, characterized in that: In step 2), the mass ratio of the mixture of tin tetrachloride pentahydrate and thioacetamide to the carbon nanotubes is 1:0.1-1:1; Preferably, in the mixture of tin tetrachloride pentahydrate and thioacetamide, the mass ratio of the tin tetrachloride pentahydrate to the thioacetamide is 1:0.6-1:1.
5.
4. The preparation method according to claims 1-3, characterized in that: In step 3), the temperature of the hydrothermal reaction is 100-200° C., and the reaction time is preferably 10-24 hours.
5. The preparation method according to claims 1-3, characterized in that: In the step 1), the activation treatment comprises: The carbon nanotubes are mixed with hydrochloric acid in a mass ratio of 0.5:1 to 1:1, treated in an air atmosphere for 1 to 6 hours, and then washed with deionized water; Preferably, the activation treatment is carried out at room temperature; Preferably, the concentration of the hydrochloric acid is 0.2-1 mol / L.
6. The preparation method according to any one of claims 1 to 3, characterized in that: In step 3), the high temperature carbonization is carried out for 1-6 hours.
7. The preparation method according to any one of claims 1 to 3, characterized in that: In step 3), the thickness of the carbon layer is 2-10 nm.
8. A carbon nanotube / tin disulfide@carbon composite material, characterized in that: The composite material comprises a carbon nanotube / tin disulfide substrate, the surface of the substrate is coated with a carbon layer, and the thickness of the carbon layer is preferably 2-10 nm; Preferably, the carbon nanotube / tin disulfide substrate is obtained by in-situ growing tin disulfide on the surface of carbon nanotubes; Preferably, the carbon layer is formed by carbonization of glucose and / or sucrose, preferably the carbon layer is formed by carbonization of glucose; Further preferably, the composite material is prepared by the preparation method according to any one of claims 1-7.
9. Use of the carbon nanotube / tin disulfide@carbon composite material obtained by the preparation method according to any one of claims 1 to 7 or the carbon nanotube / tin disulfide@carbon composite material according to claim 8, characterized in that: The composite material is used as a negative electrode material, preferably as a negative electrode material for a lithium ion battery.
10. A lithium ion battery, characterized in that: The negative electrode material used in the lithium-ion battery includes the carbon nanotube / tin disulfide@carbon composite material prepared by the preparation method described in any one of claims 1 to 7 or the carbon nanotube / tin disulfide@carbon composite material described in claim 8.
